Deregulation of Nrf2/ARE signaling pathway causes susceptibility of dystrophin-deficient myotubes to menadione-induced oxidative stress - Choi, Su Jin; Kim, Hye Sun (Experimental Cell Research, 2018)
Duchenne muscular dystrophy (DMD) is an X chromosome-linked disorder caused by a mutation in the dystrophin gene. Many previous studies reported that the skeletal muscles of DMD patients were more susceptible to oxidative stress than those of healthy people. However, not much has been known about the responsible mechanism of the differential susceptibility. In this study, we established dystrophin knock-down (DysKD) cell lines by transfection of dystrophin shRNA lentiviral particles into C2 cells and found that DysKD myotubes are more vulnerable to menadione-induced oxidative stress than control myotubes. We focused on the nuclear erythroid 2-related factor 2 (Nrf2) which is a transcription factor that regulates the expression of phase II antioxidant enzymes by binding to the antioxidant response element (ARE). Under menadione-induced oxidative stress, the translocation of Nrf2 to the nucleus is significantly decreased in the DysKD myotubes. In addition, the binding of Nrf2 to ARE site of Bcl-2 gene as well as protein expression of Bcl-2 is decreased compared to the control cells. Interestingly, sulforaphane increased Akt activation and Nrf2 translocation to the nucleus in the DysKD myotubes. These results suggest that the Nrf2 pathway might be the responsible pathway to the oxidative stress-induced muscle damage in DMD.
Keywords: Antioxidant Response Elements; Cell Survival; Dystrophin; Humans; Muscle Fibers, Skeletal; Muscular Dystrophy, Duchenne; NF-E2-Related Factor 2; Oxidative Stress; Signal Transduction; Vitamin K 3; Dystrophin; Menadione; Nrf2; Oxidative stress; PI3-kinase/Akt signaling; Sulforaphane; Translocation